Bano Qudsia’s Female Characters through the Eyes of Male Characters - Shakil Ahmad; Ijaz Ahmad Jan (Journal of Religion and Society, 2026)
This study examines the presentation of male characters in the novels of Bano Qudsia from a feminine point of view. The central purpose is to know whether these characters depict patriarchal dominance or the traditional masculine hierarchy has been corrupted for unorthodox masculine despotism. For this purpose, in-depth textual analysis has been carried out to bring to light the behavior, dialogue, and interpersonal relationships of the characters for understanding gender power and differences. Analysis clearly clarifies the patriarchal presentation of the characters by Bano Qudsia. Male characters in Bano’s novels are independent, decision-makers, and controllers of the society that causes strengthening the patriarchal body of the society and the traditional gender roles of females are further cemented where feminine roles are only of secondary importance. Keywords: Dominance, independent society. Masculine hierarchy, unorthodox masculine,